Synthesis and evaluation of analogs of tetracyclic Ganoderma alkaloids as inhibitors of the enzyme α-glucosidase - Cala Gómez, Luis Javier (2025)
A series of synthetic analogs of tetracyclic Ganoderma alkaloids have been prepared in short sequences and in moderate overall yields by reaction of 3-formylchromene derivatives with enamines prepared from cyclic 1,3-dicarbonyl compounds. A single-crystal X-ray analysis of one of the tetracyclic products confirmed that they embody original tetrahydro-6Hchromeno[4,3-b]quinoline (and tetrahydrochromeno[4,3-b] cyclopenta[e]pyridine) skeletons. When tested as α-glucosidase inhibitors, the analogs proved to be up to 40 times more potent than acarbose, used as reference inhibitor.